Combine Effect of Vitamin C and Cadmium on the Aminoacid Content of Citrobacter Freundii - İbrahim, Muhammad Salihu; Çakmak, Meltem; Özer, Dursun; Karatas, Fikret; Saydam, Sinan (My University, 2021)
In this study, Citrobacter freundii was grown in LB medium containing different concentrations of cadmium. Then, vitamin C were added to the medium containing cadmium and amino acids content of bacteria were determined by HPLC. It was observed that, the amount of amino acids in C. freundii grown in LB medium, containing 75, 100 and 125 ppm cadmium were compared with the control, the amounts of alanine, arginine, asparagine, aspartic acid, cysteine, glycine, histidine, isoleucine, leucine, lysine, phenylalanine, proline, threonine, tyrosine and valine increased (p<0.05), glutamic acid, glutamine, methionine, serine and tryptophan levels were decreased p<0.05). With the addition of vitamin C to the growth medium of bacteria containing cadmium, showed that some of the amino acids concentrations increasing, rest of the amino acid studied were observed to be decreasing. From these findings, it can be said that the negative effect of cadmium on C. freundii is reduced by the addition of vitamin C to the medium. In short vitamin C reversed the effect of cadmium on the amino acid content of bacteria.
Keywords: Cadmium; C. Freundii